First records of two siluriform fishes: Bagrichthys micranodus (Actinopterygii: Siluriformes: Bagridae) and Pangasianodon hypophthalmus (Pangasiidae) from Sumatra, Indonesia - Kunto Wibowo; Muslim Muslim; Muhammad Afrisal; Agus Priyadi; Ruby V. Kusumah; Lukman Lukman (Acta Ichthyologica et Piscatoria, 2024)
A bagrid catfish, Bagrichthys micranodus Roberts, 1989, has been reliably reported only from Borneo Island, whereas a pangasiid catfish, Pangasianodon hypophthalmus (Sauvage, 1878), originally from the Mekong and Chao Phraya rivers, has been widely introduced for aquaculture throughout southeast Asia. However, an ichthyofaunal survey of Cala Lake, South Sumatra, disclosed significant distribution extensions for both species, that of B. micranodus being the first from a land mass other than Borneo Island. Additionally, P. hypophthalmus was recorded from a natural freshwater habitat, outside the controlled environments of aquaculture facilities. The specimens are described in detail and comparisons are made with closely related species.